Distinctive lung cancer incidence trends among men and women attributable to the period effect in Shanghai: An analysis spanning 42 years. (19th February 2020) - Xie, Li; Qian, Ying; Liu, Yishan; Li, Yixuan; Jia, Sinong; Yu, Herbert; Wang, Chunfang; Qian, Biyun; Bao, Pingping
Abstract: Background: Many previous studies reported secular trend of lung cancer incidence and mortality, but little is known about the possible reasons for these trends. Methods: Data were obtained from Shanghai Cancer Registry. Age‐standardized rates were calculated and average annual percent changes (AAPCs) were evaluated by Joinpoint regression. Age, period, and birth cohort effects were assessed by age‐period‐cohort models. Results: From 1973 to 2010, compared with long‐time slowly increasing trend in women, male lung cancer incidence had significantly decreased between 2001 and 2009. After that lung cancer incidence rising sharply in women (AAPC = 14.13%, 95%CI: 2.68%‐26.86%, P  = .016) and similar rising trends without statistical significance in men (AAPC = 2.96, 95%CI: −2.47%‐8.69%, P  = .281) between 2010 and 2014. Age‐period cohort model showed the different patterns of period effects for lung cancer incidence between men and women. The period effects for lung cancer incidence showed rising effect for women, whereas there was decline effect for lung cancer incidence for men. On the other hand, the model showed a significant period effect in both genders with a similar fashion in mortality, yielding steady falling trends during the entire study period. Conclusions: The distinctive patterns of lung cancer incidence between men and women may be attributable to significant period effects, which reflected the changes in public health policies or diagnostic practices and highlighted the urgent of continued monitoring of gender‐specific risk factors for lung cancer incidence. Abstract : This study found that distinctive patterns of lung cancer incidence between male and female may be attributable to significant period effects, which reflect the effectiveness of primary prevention measures and highlighted the urgent of continued monitoring of gender‐specific risk factors for lung cancer incidence.